Recontextualizing Arabic Reading Instruction: Developing Arabic Reading Skills Teaching Materials Grounded in Islamic Values - Hamidah,; Abdullah, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to develop Maharah al-QirÄâ€™ah (Arabic reading skills) instructional materials that integrate Islamic values and are contextualized to studentsâ€™ social and proficiency levels. Utilizing a Research and Development (R&D) approach adapted from the Borg & Gall model, the research followed eight key stages, including preliminary research, planning, product development, field testing, revision, and implementation. Conducted at a single Islamic higher education institution, the study found that the developed materials significantly improved studentsâ€™ reading comprehension of Arabic texts and positively influenced their affective and social engagement, including motivation and active participation. Validation by experts confirmed the materialsâ€™ feasibility, with recommendations for refining text structure and grammar. Theoretically, this research contributes to the Value-Based Content and Language Integrated Learning (VB-CLIL) paradigm by positioning Arabic reading instruction as a vehicle for values education, character building, and Islamic identity formation. The developed model is adaptable for implementation across similar Islamic educational contexts.